2007
DOI: 10.1002/jts.20197
|View full text |Cite
|
Sign up to set email alerts
|

Aggression among combat veterans: Relationships with combat exposure and symptoms of posttraumatic stress disorder, dysphoria, and anxiety

Abstract: Prior research has revealed heightened aggressive behavior among veterans with PTSD. This study tested a model examining the interrelationships among combat exposure, posttraumatic stress disorder (PTSD) symptoms, dysphoric symptoms, and anxiety symptoms in predicting aggressive behavior in a sample of 265 male combat veterans seeking diagnostic assessment of PTSD. Combat exposure was indirectly associated with aggression primarily through its relationship with PTSD symptoms. Symptoms of PTSD were directly rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
116
4
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(128 citation statements)
references
References 48 publications
5
116
4
3
Order By: Relevance
“…Forty percent of the 10 patients who had a diagnosis of both dementia and PTSD were aggressive, which was similar to the 41% incidence of aggression in the 205 patients who had dementia without a comorbid diagnosis of PTSD. These findings are inconsistent with data from previous researchers (Kulka et al, 1990;Lasko et al, 1994;Beckman et al, 1997;McFall et al, 1999;Begic and Jokic-Begic, 2001;Taft et al, 2007a;Taft et al, 2007aTaft et al, , 2007b. Some studies suggest that increased severity of PTSD symptoms is associated with an increased risk of aggression (Byrne and Riggs, 1996;O'Donnell et al, 2006).…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Forty percent of the 10 patients who had a diagnosis of both dementia and PTSD were aggressive, which was similar to the 41% incidence of aggression in the 205 patients who had dementia without a comorbid diagnosis of PTSD. These findings are inconsistent with data from previous researchers (Kulka et al, 1990;Lasko et al, 1994;Beckman et al, 1997;McFall et al, 1999;Begic and Jokic-Begic, 2001;Taft et al, 2007a;Taft et al, 2007aTaft et al, , 2007b. Some studies suggest that increased severity of PTSD symptoms is associated with an increased risk of aggression (Byrne and Riggs, 1996;O'Donnell et al, 2006).…”
Section: Discussioncontrasting
confidence: 61%
“…One particular issue is the role of other psychiatric comorbidities in relationship to aggression. Previous studies have elucidated the high association of mood and anxiety disorders with PTSD (Orsillo et al, 1996;Mittal et al, 2006;Taft et al, 2007a). Based on a population of veterans in a database at the Boston VA Medical Center, 98% of veterans were found to have a comorbid axis I disorder in their lifetime.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An association between symptoms of PTSD and both general and partner aggression has been consistently demonstrated in Veteran and civilian populations [22,[28][29][30][31][32][33]. In the nationally representative National Vietnam Veterans Readjustment Study [34], 13.5 percent of Veterans without PTSD were identified as partner-violent during the previous year, whereas 33 percent of Veterans with PTSD perpetrated violence [35].…”
Section: Ptsd and Aggressionmentioning
confidence: 99%
“…Increasingly, the hyperarousal cluster has been shown to be most strongly associated with aggression [30,39]. In an analysis of the effect of each of the symptom clusters on general physical aggression in 1,328 male Vietnam Veterans, Taft et al showed a negative association between avoidance/numbing symptoms and aggression, and re-experiencing symptoms were only indirectly associated with aggression through a positive relationship with physiological reactivity and a negative relationship with alcohol problems [30]. In contrast, hyperarousal symptoms had a significant positive relationship with aggression.…”
Section: Ptsd and Aggressionmentioning
confidence: 99%